The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.msea.2007.01.065
|View full text |Cite
|
Sign up to set email alerts
|

A study on the SCC susceptibility of friction stir welded AZ31 Mg sheet

Abstract: In this study, the stress corrosion cracking (SCC) behavior of friction stir welded (FSW) AZ31 Mg alloy was examined using slow strain rate tensile (SSRT) test method.Electrochemical impedance spectroscopy (EIS) and salt spray tests were carried to understand the general corrosion behavior. The FSW AZ31 Mg samples exhibited higher SCC susceptibility than the base material during SSRT in corrosive environment. The failure of the FSW AZ31 Mg samples occurred in the stir zone (SZ) when tested in corrosive environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…The anodic dissolution tendency of magnesium in aqueous environments is due to its high electronegative potential and to the fact that the corrosion product/film formed on magnesium is not protective, especially in chloride-containing environment. Hence, magnesium and its alloys are susceptible to localized corrosion, such as pitting, and to SCC in chloride-containing environment [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The anodic dissolution tendency of magnesium in aqueous environments is due to its high electronegative potential and to the fact that the corrosion product/film formed on magnesium is not protective, especially in chloride-containing environment. Hence, magnesium and its alloys are susceptible to localized corrosion, such as pitting, and to SCC in chloride-containing environment [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…69 The presence of Fe as impurity plays a crucial role in SCC, especially in the impure alloys. 79 The fracture was observed at a stress level of around 100 MPa with a strain of 2% compared to the strain level of about 45% in the tests in air. 77,78 In a recent work, the SCC susceptibility of an extruded magnesium alloy (AZ31) in ASTM D 1384 test solution (Figure 12) was addressed.…”
Section: Environmentally Assisted Damagesmentioning
confidence: 89%
“…Studies have shown that the SCC of Mg alloys occurs through transgranular stress corrosion cracking (TGSCC), intergranular stress corrosion cracking (IGSCC), or a mixed TGSCC/IGSCC mode 43,44) . The mode of SCC depends on the composition 44) and microstructure 45) of the alloy and possibly on environmental factors such as pH 25) .…”
Section: Effect Of Sn Content On Crack Propagationmentioning
confidence: 99%